The interaction of attention and action: from seeing action to acting on perception. - Humphreys, G; Yoon, E; Kumar, S; Lestou, V; Kitadono, K; Roberts, K; Riddoch, M (2010)
We discuss evidence indicating that human visual attention is strongly modulated by the potential of objects for action. The possibility of action between multiple objects enables the objects to be attended as a single group, and the fit between individual objects in a group and the action that can be performed influences responses to group members. In addition, having a goal state to perform a particular action affects the stimuli that are selected along with the features and area of space that is attended. These effects of action may reflect statistical learning between environmental cues that are linked by action and/or the coupling between perception and action systems in the brain. The data support the argument that visual selection is a flexible process that emerges as a need to prioritize objects for action.